Habituasi dan Internalisasi Nilai-Nilai Pendidikan Islam dalam Pengembangan Karakter: Studi Fenomenologi di Madrasah Ibtidaiyah Nasy’atul Muta’allimin Candi Sumenep - Ach. Syaiful; Amiruddin; Hafid; Faizatul Fitriyah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
Madrasah as an Islamic educational institution faces challenges in implementing Islamic values for student character building. Although religious activities have been carried out routinely, they have not effectively touched the core of students’ spirituality as reflected in their daily behavior. The gap between the ideality of madrasah as a producer of noble character and the reality of value shifts highlights the urgency of structured and sustainable Islamic value implementation studies. This study employs a qualitative approach with ethnographic-phenomenological methods at Madrasah Ibtidaiyah Nasy’atul Muta’allimin Candi, Sumenep, Madura. Research subjects include the madrasah principal, vice principals, teachers, school committees, parents/guardians, and surrounding community. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed through data reduction, data presentation, conclusion drawing, and verification stages. Data validity was ensured through credibility, transferability, dependability, and confirmability. The findings reveal that Islamic values implementation is based on three main foundations: faith, sharia, and ihsan, manifested through habituation of greeting-smiling-salutation values, honesty, trustworthiness, and responsibility. Implementation strategies include teacher exemplary behavior, madrasah culture, project-based learning, and cross-curricular integration, reinforced with specific practices such as teachers welcoming students, reciting Asmaul Husna, congregational dhuha prayer, and intensive parental cooperation. This study concludes that Islamic character building requires continuous habituation through real behavioral examples from teachers and parents. Recommendations are directed to madrasah education practitioners to develop structured, organized, and dynamic value implementation concepts according to each institution’s factual context, and to future researchers to explore the long-term impacts of habituation strategies on madrasah students’ character.